Alpelisib-Induced Diabetic Ketoacidosis - Espinosa, Luis Borges (J Endocr Soc, 2021)
Introduction: Alpelisib is a alpha-specific phosphoinositide 3-kinase inhibitor (PI3K) recently approved for patients with advanced or metastatic breast cancer with hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative, and activating mutations in the PIK3CA gene. PI3K is involved in the insulin receptor signaling pathway that leads to glucose uptake. Hyperglycemia is a frequent adverse effect of Alpisilib but diabetic ketoacidosis (DKA) is considered a rare occurrence. Case ReportA 53 year-old woman with metastatic breast cancer presented with 5 days of worsening polydipsia, fatigue, nausea, vomiting, slurred speech and altered mental status. She was started on Alpelisib 300 mg daily two weeks prior to admission and instructed to check glucose twice weekly but did not follow directions. Family history was significant for type 2 diabetes. On physical exam blood pressure was 150/90, heart rate 120 beats/minute, respiratory rate 120 breaths/minute; BMI was 27 Kg/m2. The neurological exam was significant for a lethargic state with the patient arousable to verbal stimuli. The skin exam was negative for acanthosis nigricans or skin tags. Laboratory tests showed glucose at 1425 mg/dl, bicarbonate 11 mEq/l (19–34), anion gap 39 (6–22), sodium 138 mmol/l (135–146), potassium 5.0 mmol/l (3.5–5.5), serum osmolality 378 mosm/kg (275–295), Cr 3.99 mg/dl (0.4–1.1), lactic acid 3.5 mmol/l (0.5–2.0), ketonuria and glucosuria. No arterial blood gas was performed. HbA1c was 5.9% before starting Alpelisib. Results were consistent with DKA and hyperosmolar hyperglycemic state. Additional tests showed HbA1c 10.5 %, c-peptide 1.2 ng/ml (1.1–4.4) with glucose 183 mg/dl; type 1 diabetes autoantibodies were negative. Alpesilib was held and the patient managed with insulin drip and then insulin basal/bolus regimen. Patient was discharged on basal insulin and metformin with the plan to resume alpelisib at a lower dose and monitor. ConclusionIn the SOLAR-1 trial hyperglycemia was reported in 63% of patients taking alpesilib and two cases of DKA were observed. A case of a patient who developed DKA with Alpesilib was also recently reported. The mechanism underlying DKA in these patients is unclear. PI3K inhibitors may prevent the transcription of the insulin gene in response to high concentrations of glucose and the combination of impaired peripheral glucose uptake with impaired insulin secretion trigger DKA. Further studies are needed to identify which patients on Alpelisib are at increased risk of developing DKA. Clinicians should be aware of this life threatening complication. References: F André, et al. Alpelisib for PIK3CA-Mutated, Hormone Receptor-Positive Advanced Breast Cancer. N Engl J Med 2019; 380.SJ. Farah, et al. Diabetic ketoacidosis associated with alpelisib treatment of metastatic breast cancer. AACE Clinical Case Reports 2020; Vol. 6, No. 6.